1968
DOI: 10.1115/1.3597439
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Water Flow Over Heated and Cooled Flat Plates

Abstract: The theory of two-dimensional instability of laminar flow of water over solid surfaces is extended to include the effects of heat transfer. The equation that governs the stability of these flows to Tollmien-Schlichting disturbances is the Orr-Sommerfeld equation “modified” to include the effect of viscosity variation with temperature. Numerical solutions to this equation at high Reynolds numbers are obtained using a new method of integration. The method makes use of the Gram-Schmidt orthogonalization technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(28 citation statements)
references
References 0 publications
4
24
0
Order By: Relevance
“…It is curious that for boundary layers in water, the effect of cooling is destabilizing while the effect of heating is stabilizing (Wazzan, Okamura and Smith 1967). Because the viscosity of water decreases sharply with increase in temperature, heating yields a fuller velocity profile while cooling tends to give an inflected velocity profile.…”
Section: Results Of Normal Modes Calculationsmentioning
confidence: 99%
“…It is curious that for boundary layers in water, the effect of cooling is destabilizing while the effect of heating is stabilizing (Wazzan, Okamura and Smith 1967). Because the viscosity of water decreases sharply with increase in temperature, heating yields a fuller velocity profile while cooling tends to give an inflected velocity profile.…”
Section: Results Of Normal Modes Calculationsmentioning
confidence: 99%
“…[13][14][15] Wall and Wilson 15 studied the influence of continuous viscosity variation due to a temperature gradient in a rigid channel and showed that the Péclet number has little influence on the stability and that the base state viscosity influences the Tollmien-Schlichting (TS) mode. The experiments [16][17][18][19][20] on miscible two-fluid flow in different geometries revealed interesting instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Farther downstream, the boundary layer became unstable, causing amplification and eventual breakdown of the waves. Since the stability of the boundary layer to small disturbances is greatly affected by the pressure gradient (Wazzan et al 1968), the same may hold for the amplification of the wave packet accompanying the spot. Some aspects of the experiment were therefore repeated in the presence of a slightly favorable pressure gradient for the purpose of delaying the breakdown process.…”
Section: Experiments At 8 -02mentioning
confidence: 99%